Schlieren methods for high pressure turbulent jet flames - Li, L.; Fu, Shan; Witton, John J. (Cranfield University, 2009)
Turbulent flame speeds of a premixed synthetic natural gas mixture were measured using a jet flow apparatus over a range of pressures to 0·8 MPa at an equivalence ratio of 0·9. The method adopted was the 'flame angle' technique, using schlieren imaging to obtain the flame vertex angle from the peak density gradient. Image analysis techniques were developed to reduce interpretation errors and to give information on the velocity and combined gradient distribution local to the flame fron
Keywords: Flame speed, Schlieren, Optical methods, Image analysis, Combustion